The Relationship Between Religion and Attitudes Toward Large Carnivores in Northern India?. Issue 1 (2nd January 2017) - Bhatia, Saloni; Redpath, Stephen Mark; Suryawanshi, Kulbhushansingh; Mishra, Charudutt
ABSTRACT: Evidence suggests that religion is an important driver of peoples' attitudes toward nature, but the link between religion and carnivore conservation is poorly understood. We examined peoples' attitudes in Buddhist ( n  = 83) and Muslim communities ( n  = 111) toward snow leopards ( Panthera uncia ) and wolves ( Canis lupus ) in Ladakh, India. We found that the effect of religion on attitudes was statistically nonsignificant, and was tempered by gender, education, and awareness of wildlife laws. Even though religion by itself was not an indication of an individual's attitude toward large carnivores, the extent to which he/she practiced it (i.e., religiosity) had a positive correlation with pro-carnivore attitudes in the case of Buddhist but not Muslim communities. Our findings indicate that it may be useful to integrate locally relevant religious philosophies into conservation practice. However, the emphasis of conservation messaging should vary, stressing environmental stewardship in the case of Islam, and human–wildlife interdependence in the case of Buddhism.